2021
DOI: 10.1186/s12872-021-01890-1
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization of the occluded radial artery via distal transradial access in the anatomic snuffbox

Abstract: Background Radial artery occlusion is a common complication after coronary angiography and percutaneous coronary intervention via the transradial access. In recent years, coronary angiography and percutaneous coronary intervention via the distal transradial access has gradually emerged, but recanalization of the occluded radial artery through the distal transradial access has rarely been reported. Case presentation A 67-year-old female with arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The left-hand snuffbox approach is preferred because it uses the patient's nondominant hand (in most cases), and the operator can use the right hand to perform fine movements, such as in the femoral access. Besides, the operator's distance from the fluoroscope is safer [15] . If left-handed access is selected, the patient's arm can be placed over the body with the operator on the right side.…”
Section: Discussionmentioning
confidence: 99%
“…The left-hand snuffbox approach is preferred because it uses the patient's nondominant hand (in most cases), and the operator can use the right hand to perform fine movements, such as in the femoral access. Besides, the operator's distance from the fluoroscope is safer [15] . If left-handed access is selected, the patient's arm can be placed over the body with the operator on the right side.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only four previous reports tested the feasibility of RAO recanalization via DRA [ 12 , 13 , 14 , 15 ]. Gasparini et al described the same technique of balloonless dilatation and wiring directly through the needle [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the adoption of DRA, attempts to recanalize recent or chronic RAO have also increased, with promising results, but reporting is limited to case reports or case series [ 12 , 13 , 14 , 15 ]. The conclusion of these publications called for larger registries to investigate the prevalence of complications of radial angioplasty (perforation, hematoma, digital ischemia, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Sheikh et al (11) reported a successful angioplasty via dTRA in recanalizing the left RAO of a 75-year-old man with a medical history of coronary artery bypass, previous multiple PCIs, and severe peripheral vascular disease. Li et al (12) presented a case of RAO after emergency CAG and PCI in which recanalization was successfully performed through dTRA access. Additionally, case series have suggested that dTRA was safe and convenient for retrograde recanalization of RAO, with success rates of 88 to 93% (4,5).…”
Section: Discussionmentioning
confidence: 99%